The Effect of Clarity of Budget Goals, Effectiveness of Internal Accounting Control and Budget Participation on Performance Accountability: Pengaruh Kejelasan Sasaran Anggaran , Efektifitas Pengendalian Internal Akuntansi dan Partisipasi Anggaran Terhadap Akuntanbilitas Kinerja - M. Ilham Musthofa; Sarwenda Biduri (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the effect of the clarity of budget targets, the effectiveness of internal accounting controls and budget participation on performance accountability (in the regional work unit (SKPD) of Sidoarjo Regency). The sampling method used is a saturated sampling technique because the population is relatively small. The sample in this study were 84 respondents. Each service is represented by 4 people, namely the head of the section and staff of the accounting or financial administration department at the SKPD of Sidoarjo Regency. The data used is secondary data. The data analysis method used in this study is Multiple Linear Regression with SPSS 23. The results of this study indicate that the Clarity of Budget Targets has an effect on Performance Accountability. Effectiveness of Accounting Internal Control has an effect on Performance Accountability. Budget Participation has an effect on Performance Accountability.